Reconstruction of the Foot Using a Superficial Inferior Epigastric Artery Free Flap - Jin Ho Han; Hyun Woo Shin; Kun Chul Yoon; June-Kyu Kim (Archives of Plastic Surgery, 2017)
When foot reconstruction is performed in the pretibial area, the ankle, or the dorsum of the foot, the need for a reliable flap remains a challenge. We found that the superficial inferior epigastric artery (SIEA) free flap can be used as an alternative tool for this purpose, as it helps to solve the problems associated with other flaps. We describe 2 cases in which we reconstructed the foot using an SIEA free flap, which was pliable enough to fit the contours of the area. Postoperatively, the flaps were intact and showed excellent aesthetic results. Thus, the SIEA free flap can be an alternative tool for patients with a low body mass index who undergo reconstructive surgery involving the pretibial area, ankle, knee, or dorsum of the foot, all of which require a soft and flexible flap.